Long‐term results of combined cardiac contractility modulation and subcutaneous defibrillator therapy in patients with heart failure and reduced ejection fraction. Issue 4 (26th April 2018) - Röger, Susanne; Rudic, Boris; Akin, Ibrahim; Shchetynska‐Marinova, Tetyana; Fastenrath, Fabian; Tülümen, Erol; Liebe, Volker; El‐Battrawy, Ibrahim; Baumann, Stefan; Kuschyk, Jürgen; Borggrefe, Martin
Abstract : Background: Cardiac contractility modulation (CCM) is an electrical‐device therapy for patients with heart failure with reduced ejection fraction (HFrEF). Patients with left ventricular ejection fraction (LVEF) ≤35% also have indication for an implantable cardioverter‐defibrillator (ICD), and in some cases subcutaneous ICD (S‐ICD) is selected. Hypothesis: CCM and S‐ICD can be combined to work efficaciously and safely. Methods: We report on 20 patients with HFrEF and LVEF ≤35% who received CCM and S‐ICD. To exclude device interference, patients received intraoperative crosstalk testing, S‐ICD testing, and bicycle exercise testing while CCM was activated. Clinical and QOL measures before CCM activation and at last follow‐up were analyzed. S‐ICD performance was evaluated while both CCM and S‐ICD were active. Results: Mean follow‐up was 34.3 months. NYHA class improved from 2.9 ± 0.4 to 2.1 ± 0.7 ( P < 0.0001), Minnesota Living With Heart Failure Questionnaire score improved from 50.2 ± 23.7 to 29.6 ± 22.8 points ( P < 0.0001), and LVEF improved from 24.4% ± 8.1% to 30.9% ± 9.6% ( P = 0.002). Mean follow‐up time with both devices active was 22 months. Three patients experienced a total of 6 episodes of sustained ventricular tachycardia, all successfully treated with first ICD shock. One case received an inappropriate shock unrelated to the concomitant CCM. One patient received an LVAD, so CCM and S‐ICD were discontinued. Conclusions: CCM and S‐ICD can be successfully combined in patients with HFrEF. S‐ICD and CCM remain efficacious when used together, with no interference affecting their function.